Follow-up bone scintigraphy images of a patient with osteoid osteoma during medical treatment - Koç, Zehra Pinar; Karayalcin, Binnur (BMJ Publishing Group, 2012)
Osteoid osteoma is a benign bone tumour which is usually seen in long bones. Although the eventual treatment of this tumour is surgery, medical treatment is another option. We present the 3 years follow-up bone scintigraphy images of a patient with osteoid osteoma which show improvement by medical treatment. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: antiinflammatory agent; naproxen; adult; article; bone radiography; bone scintiscanning; bone tumor; case report; computer assisted tomography; female; human; nuclear magnetic resonance imaging; osteoid osteoma; positron emission tomography; priority journal; treatment response